(untitled) (International journal of artificial intelligence, 2026)
The article presents a literature review of innovative mechanisms for continuous professional education ( Continuous Professional Development ( CPD ) of employees of the human resources development and management service in the healthcare system. Based on an analysis of domestic and international scientific publications, regulatory documents of the Republic of Uzbekistan, and international recommendations of the World Health Organization (WHO), modern CPD models and tools are systematized . Digital educational platforms, microlearning , microcredit systems, adaptive and simulation technologies, and blended learning are considered. The relevance of developing a comprehensive system of continuous professional development for HR specialists is substantiated as a key factor in improving the effectiveness of HR policy and the sustainable development of healthcare.